Transcriptome and Metabonomics Combined Analysis Revealed the Defense Mechanism Involved in Hydrogen-Rich Water-Regulated Cold Stress Response of Tetrastigma hemsleyanum - Liu, Yuxiu; Pan, Junjie; Ni, Sui; Xing, Bincong; Cheng, Kejun; Peng, Xin (Frontiers in Plant Science, 2022)
The poor resistance to cold stress conditions has become the bottleneck problem in Tetrastigma hemsleyanum (T. hemsleyanum) planting industry. Exogenous hydrogen (H2) plays an important role in improving stress resistance in plants. However, the key factors and regulatory network of plants in response to hydrogen-rich water (HRW) treatment under environmental stress are not clear. Here, we conducted integrative analyses of metabolome and transcriptome profiles to reveal the defense mechanism involved in the HRW-regulated cold stress response of T. hemsleyanum. The application of 75% HRW could alleviate stress damage by decreasing stomatal apparatus density and significantly increasing photosynthetic efficiency and mitigating physiological indexes of resistance, such as Pn, Cond, MDA, SOD, etc., which were changed by cold stress conditions. A total of 7,883 DEGs and 439 DEMs were identified. DEGs were the most relevant to phenylpropanoid, isoflavonoid, monoterpenoid, and flavonoid biosynthesis pathways. Using gene co-expression analysis (WGCNA), we identified one gene module that showed a strong correlation between total antioxidant capacity and transpiration rate. Trend analysis indicated that the phenylpropanoid biosynthesis pathway played a major role in the transcription and metabolism process of HRW treatment under cold stress. Based on the integrated analysis of genes and metabolites, the results showed cold stress upregulated the expression of PAL, CHS, COMT, CCR, AtBG1, etc., resulting in the accumulation of coniferyl alcohol and eriodictyol contents in T. hemsleyanum under cold stress, but the 75% HRW treatment could attenuate the enhancement. The study not only identified the main strategy of HRW protection against cold stress but also provided candidate genes for flavonoid biosynthesis, so as to better improve cold tolerance through molecular breeding techniques.